Regulation of small GTP-binding proteins by insulin. (20th March 2006) - Welsh, G.I.; Hers, I.; Wherlock, M.; Tavaré, J.M.
Abstract : Several members of the extensive family of small GTP-binding proteins are regulated by insulin, and have been implicated in insulin action on glucose uptake. These proteins are themselves negatively regulated by a series of specific GAPs (GTPase-activating proteins). Interestingly, there is increasing evidence to suggest that PKB (protein kinase B)-dependent phosphorylation of some GAPs may relieve this negative regulation and so lead to the activation of the target small GTP-binding protein. We review recent evidence that this may be the case, and place specific emphasis on the role of these pathways in insulin-stimulated glucose uptake.